Interplay between influenza virus and the host RNA polymerase II transcriptional machinery - Walker, A; Fodor, E (Cell Press, 2019)
The influenza virus RNA-dependent RNA polymerase (RdRP) cleaves the 5′ end of nascent capped host RNAs and uses the capped RNA fragment to prime viral transcription in a mechanism called ‘cap snatching’. Cap snatching requires an intimate association between influenza RdRP and cellular RNA polymerase II (Pol II), which is the source of nascent capped host RNAs targeted by influenza virus. Recent structural studies have revealed how influenza RdRP binds to Pol II and how this binding promotes the initiation of viral transcription by influenza RdRP. In this review we focus on these recent insights into the mechanism of cap snatching by influenza virus and the impact of cap snatching on host gene expression during influenza virus infection.